2002
DOI: 10.1002/1521-3757(20020902)114:17<3260::aid-ange3260>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Die biologische und medizinische Bedeutung von Calciumphosphaten

Abstract: Die anorganische Komponente der Hartgewebe (Knochen und Zähne) von Säugetieren besteht aus Calciumphosphat, hauptsächlich aus Hydroxylapatit. Auch die meisten pathologischen Verkalkungen, die zu oft schweren Erkrankungen führen, beruhen letztlich auf der Kristallisation von Calciumphosphaten an unerwünschten Orten im Körper. Medizinisch wichtig ist hier vor allem die Arteriosklerose, d. h. die Blockierung von Blutgefäßen durch Cholesterin und Calciumphosphate. Die Kariesbildung beruht auf dem Ersatz des wenig … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 243 publications
(237 reference statements)
1
42
0
4
Order By: Relevance
“…With the exception of enamel, they are always found as nanoparticles [69][70][71]. Sokolova et al [72] reported that DNA-coated calcium phosphate nanoparticles could be stored for weeks without loss of their transfection efficiency.…”
Section: Calcium Phosphatementioning
confidence: 99%
“…With the exception of enamel, they are always found as nanoparticles [69][70][71]. Sokolova et al [72] reported that DNA-coated calcium phosphate nanoparticles could be stored for weeks without loss of their transfection efficiency.…”
Section: Calcium Phosphatementioning
confidence: 99%
“…[6][7][8] As an important inorganic component of biological hard tissues, such as bones and teeth, 9,10 hydroxyapatite [Ca 10 (PO 4 Þ 6 (OH) 2 , HAp] has attracted much attention as an excellent candidate for biomedical applications, owing to its outstanding biocompatibility. 11,12 Many e®orts have been made toward fabricating HAp-based nanostructures because of their promising applications in arti¯cial bones, 13,14 drug deliveries, 15 catalysts, 16 sensors, 17 photoelectric materials, 18 chemical and environmental engineering. [19][20][21] The performance of HAp in above applications depends greatly on its crystallite size, chemical compositions, three-dimensional (3D) architectures and morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Due to its chemical similarity to the inorganic constituent of human bone and tooth, synthetic CP has outstanding biocompatibility, good biodegradability, essentially no toxicity, and high chemical and thermal stability. [7,8] Due to its chemical similarity to the inorganic constituent of human bone and tooth, synthetic CP has outstanding biocompatibility, good biodegradability, essentially no toxicity, and high chemical and thermal stability.…”
Section: Introductionmentioning
confidence: 99%